PHYSICAL REHABILITATION FOR CHILDREN WITH ERB’S PALSY: A SYSTEMATIC REVIEW - DZULKIFLI, NURUL HAFIZAH; AZIZAN, AZLIYANA; ABDUL RAHMAN, ROZLIN (International Journal of Allied Health Sciences, 2022)
Introduction: Early physical therapy intervention has a significant impact on improving the impairments and disabilities of Erb’s palsy patients. Proper assessments and management by physical therapists can reduce physical complications and mental health problems, thus enhancing the child’s opportunities to return to their maximal activity daily living. Aim: This review aims to identify the physical rehabilitation treatments available for children with Erb’s palsy. Method: This objective is fulfilled using systematic review following the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guideline. Results: The search from Web of Sciences (WoS), PubMed, Science Direct, Scopus, PEDro, Google Scholar and Clinical Trials databases yielded 245 records. 29 full-text articles were assessed and 6 eligible articles were further reviewed. Conclusion: The study summarised that physical therapy treatments should be started as early as the condition being diagnosed. Treatment is more effective when conventional physical therapy treatments are combined with advanced exercise consisting of plyometric, modified constrained induced movement therapy (MCIMT) or virtual reality (VR). This review enables physical therapists in Malaysia to plan proper and suitable treatments for Erb’s palsy patients according to the injury level and severity. KEYWORDS: Erb’s palsy, physical therapy, conventional treatment, advanced exercise